2019
DOI: 10.1103/physrevb.100.075430
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Monte Carlo study of O2 adsorption on single layer graphene

Abstract: Diffusion Monte Carlo (DMC) calculations were performed for an accurate description of the nature of the O 2 adsorption on a single layer graphene. We investigated the stable orientation of O 2 at a specific adsorption site as well as its equilibrium adsorption energy. At equilibrium adsorption distances, an O 2 molecule was found to prefer a horizontal orientation, where the O-O bond is parallel to the graphene surface, to the vertical orientation. However, the vertical orientation is favored at the O 2 -grap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…56 The DMC calculations were performed using the branching scheme proposed by Zen et al (ZSGMA) 57 with a population control target of 8,192 walkers and a time step of 0.005 a.u., which represented a balance between computational cost and finite timestep error in previous work. 58 We define the binding energy as,…”
Section: B Quantum Monte Carlo Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…56 The DMC calculations were performed using the branching scheme proposed by Zen et al (ZSGMA) 57 with a population control target of 8,192 walkers and a time step of 0.005 a.u., which represented a balance between computational cost and finite timestep error in previous work. 58 We define the binding energy as,…”
Section: B Quantum Monte Carlo Calculationsmentioning
confidence: 99%
“…To bring these applications to fruition, a deeper understanding of the interaction of atoms and molecules with graphene is required, and, not surprisingly, this has been the subject of several experimental and theoretical studies. [1][2][3][4][5][6][7][8][9][10][11][12][13] The adsorption of H atoms on graphene has been the subject of multiple studies. 3,[10][11][12][13][14] It is known that there is both a weakly absorbed state in which barriers for diffusion are small and a much more strongly bound chemisorbed state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,33 It is also suggested that Si-doped surfaces can be a metal-free catalyst for oxygen reduction reactions (ORRs). 33 Diffusion Monte Carlo (DMC) calculations were also performed for O 2 adsorption on single-layer graphene 31 to describe the adsorption's nature accurately. They have obtained adsorption energy of −0.142 eV, close to the experimental value of −0.15 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Using the computational rstprinciples technique, Nakamura et al 26 found that oxygen atoms selectively adsorb on intrinsic graphene, forming epoxide rings and modifying structural and electrical characteristics. There have been a few experimental 5,[27][28][29] and theoretical attempts 13,16,[30][31][32][33][34][35][36][37] to explore the sensing of molecular dioxygen, O 2 , on pristine and doped graphene monolayers. Some earlier literature reveals attempts to make oxygen sensors 27,28 with monolayer graphene.…”
Section: Introductionmentioning
confidence: 99%